2011
DOI: 10.1088/0031-9155/56/3/020
|View full text |Cite
|
Sign up to set email alerts
|

Development of a platform for co-registered ultrasound and MR contrast imagingin vivo

Abstract: Imaging of the microvasculature is often performed using contrast agents in combination with either ultrasound (US) or magnetic resonance (MR) imaging. Contrast agents are used to enhance medical imaging by highlighting microvascular properties and function. Dynamic signal changes arising from the passage of contrast agents through the microvasculature can be used to characterize different pathologies; however, comparisons across modalities are difficult due to differences in the interactions of contrast agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…From the figure, we could also find that the registration deviation of our method was less than the registration deviation of Beattie's and Chandrana's methods. 10,11 With these experiments, we found that the average registration deviation using the registration method based on the marked Table 1 The registration results of three mice using the two registration methods. Note: IOP stands for the registration results of three mice using our registration methods based on the iterated optimal projection; MP stands for the registration results of three mice using the registration algorithm based on the marked points.…”
Section: Registration Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…From the figure, we could also find that the registration deviation of our method was less than the registration deviation of Beattie's and Chandrana's methods. 10,11 With these experiments, we found that the average registration deviation using the registration method based on the marked Table 1 The registration results of three mice using the two registration methods. Note: IOP stands for the registration results of three mice using our registration methods based on the iterated optimal projection; MP stands for the registration results of three mice using the registration algorithm based on the marked points.…”
Section: Registration Resultsmentioning
confidence: 92%
“…All of these results showed that our registration method was more stable than the registration method based on the marked points. 10,11 Furthermore, the bioluminescence distribution derived from the four-orientation 2-D images was mapped onto the 3-D surface of the mouse derived from the Micro-CT image using our registration method based on the iterated optimal projection. The 3-D bioluminescence distribution of transgenic mouse 1 after mapping based on the registration results using our registration method is shown in Fig.…”
Section: Registration Resultsmentioning
confidence: 99%
See 3 more Smart Citations